Novel bioactive formulation derived from the conditioned medium of mesenchymal stromal cells reduces under‐eye dark circles in human volunteers. (21st April 2021) - Bhat, Samatha; Amirthalingam, Muthukumar; Ballambat, Sathish Pai; Bhupasandra Vasudev, Meghana; Gupta, Pawan Kumar; Padya, Bharath Singh; Mutalik, Srinivas; Seetharam, Raviraja N.
Abstract: Background: Under‐eye dark circles are a common condition observed in dermatology practice. Mesenchymal stromal cell‐derived conditioned medium (MSC‐CM) contains an array of growth factors and cytokines reported to promote periorbital rejuvenation and may be useful in removing the dark circle around the eyes. Aims: The aim of the present study was to evaluate the safety and efficacy of developed bioactive formulation containing mesenchymal stromal cell‐derived conditioned medium in reducing the under‐eye dark circles. Patients/Methods: We tested the safety profile of MSC‐CM along with antioxidants, in vitro using human melanocytes cultures. The bioactive formulation containing MSC‐CM was developed and tested for physicochemical parameters. The dermatological safety was evaluated by primary irritant patch‐test under complete occlusion on healthy human subjects. To elucidate its safety and efficacy, monocentric, open‐label, single‐arm study was carried out in 20 Indian female subjects for the duration of 12 weeks. Parameters such as eye puffiness, radiance, skin smoothness, even skin tone, periorbital fine lines and wrinkles, crow's feet, whitening, pigmentation, skin tightening, and refreshing/soothing effect were used to investigate the rejuvenating property of the bioactive formulation. Results: Mesenchymal stromal cell‐derived conditioned medium along with antioxidants decreased the melanin content compared to the CM alone in the melanocyte cultures. Besides, the bioactive formulation was safe and emerged as a non‐irritant product. Improvement in the majority of the clinical parameters assessed through efficacy study was observed within 4 weeks of topical application of the formulation twice daily, and showed continued improvement for 12 weeks as evaluated by the dermatologists as well as self‐assessment by the subjects. Conclusion: The bioactive formulation containing MSC‐CM was safe and effective in reducing the under‐eye dark circles and was beneficial in improving the overall appearance of the eye area.